What is the impact of fitness on injury risk during police academy training? A retrospective cohort study - Colin Tomes; Ben Schram; Rodney Pope; Robin Orr (BMC, 2020)
Abstract Background In the conduct of their daily duties, law enforcement officers (LEO) are often required to perform dynamic, physically demanding tasks with little or no notice, sometimes at maximal levels of exertion. Given these requirements, training for prospective LEOs must be rigorous enough to ensure that when trainees graduate, they are competent in their response to crisis and resilient enough to maintain this for the span of their career. Therefore, based on previously reported effectiveness of fitness testing in predicting injury risk in predominantly military settings, the aim of this study was to investigate relationships between a physical ability test (PAT) and risk of injury during police recruit training. Methods Retrospective PAT results and trainee injury records were obtained from a national police department and Mann-Whitney U tests were performed to investigate fitness differences between trainees who were, or were not, injured. Significant results were tested for effect size using Cliff's delta (CD). Results Significant differences in mean performance between groups existed for the following PAT components: pushups (injured mean 32.94 ± 8.66 reps, uninjured mean 35.67 ± 9.04 reps, p = 0.01 CD + 0.11) and right-hand grip strength (injured mean 49.61 ± 12.51 kg, uninjured mean 52.12 ± 11.17 kg, p = 0.042 CD + 0.22) for all injuries; vertical jump height (injured mean 51.75 ± 7.54 cm, uninjured mean 55.06 ± 8.19 cm, p = 0.032 CD + 0.41) for lower limb injuries, and all measures of grip strength for trunk injury. Conclusions The results of this study suggest that a significant relationship between some PAT fitness components and injury risk exists during police recruit training.